1999
DOI: 10.1111/j.1749-6632.1999.tb07700.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Biological Regulation of Proteoglycan Turnover around Chondrocytes in Cartilage Explants: Implications for Tissue Degradation and Repair

Abstract: The development of clinical strategies for cartilage repair and inhibition of matrix degradation may be facilitated by a better understanding of (1) the chondrocyte phenotype in the context of a damaged extracellular matrix, and (2) the roles of biochemical and biomechanical pathways by which matrix metabolism is mediated. Using methods of quantitative autoradiography, we examined the cell-length scale patterns of proteoglycan deposition and turnover in the cell-associated matrices of chondrocytes in adult bov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 68 publications
2
39
0
Order By: Relevance
“…Sustained elevated rates of GAG release in the most aggressively loaded explants (Fig. 3) may have indicated a cellular response to matrix injury involving increased rates of matrix turnover and remodelling, as previously observed [21,22]. It may also have reflected increased passive loss of proteoglycan due to mechanical disruption of the matrix.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Sustained elevated rates of GAG release in the most aggressively loaded explants (Fig. 3) may have indicated a cellular response to matrix injury involving increased rates of matrix turnover and remodelling, as previously observed [21,22]. It may also have reflected increased passive loss of proteoglycan due to mechanical disruption of the matrix.…”
Section: Discussionsupporting
confidence: 52%
“…The apparatus consisted of a motor controller (PM50O-C, Newport Instruments, Schlieren, Switzerland) and displacement actuator (PM500-1A, Newport) mounted opposite a load cell (Sensotec Model 31, Transmetra, Schafhausen, Switzerland) in a custom built aluminum and stainless steel frame. These peak stresses were chosen because they are close to the high end of the physiological range [I21 and they are similar to those previously found to be associated with cartilage matrix and cell injury in impact [1,10,24] and sub-impact loading studies [21,22]. Preliminary control studies indicated that this range of compression parameters would provide a wide range of severity of injury to osteochondral explants, thereby allowing for the identification of thresholds at which injury occurs.…”
Section: Methodsmentioning
confidence: 99%
“…The major silverstained protein isolated by this protocol migrated at ϳ70 kDa and corresponded to the major anti-ADAMTS4 antibody-reactive species present (Fig. 1 [1][2][3][4][5]. This showed, as expected, the gradual appearance of a 65-kDa product with the electrophoretic properties of G1-NITEGE 373 .…”
Section: Adamts4 Generates Both G1-nitege and G1-vdipen-supporting
confidence: 54%
“…Aggrecan is the major cartilage hyalectan (1), which, together with the collagen network, provides this tissue with its unique mechanical properties of compressibility and stiffness (2)(3)(4). Extraction of aggrecan in its native form (5) and subsequent structural analysis (6) have revealed that the molecular organization of aggrecan is perfectly suited to its central functional role in articular cartilage.…”
mentioning
confidence: 99%
“…While the mechanism responsible for the synergistic action between injury and proinflammatory cytokines is unclear, previous studies have shown that the modest loss of GAG observed during the initial 24-hour period after mechanical injury alone was due to mechanical microdamage of the matrix instead of cellmediated proteolysis (45), since inhibitors of aggre- canases, MMPs, and cell biosynthesis could not reduce this immediate GAG loss (9). However, injury dramatically up-regulated expression of the ADAMTS-5 gene (10), and the observed release of GAG during the 2-week period following injury alone was associated in part with aggrecanase activity (23).…”
mentioning
confidence: 99%